2013
DOI: 10.1002/joc.3851
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of dynamically downscaled ensemble climate simulations for Vietnam

Abstract: This article presents an assessment of the skill of regional climate model PRECIS in simulating seasonal climate over Vietnam. The simulations were conducted at a horizontal resolution of 25 km × 25 km. The model simulations were forced by the ERA-Interim reanalysis and five members of the Hadley Centre's perturbed physics ensemble (PPE). CRU, APHRODITE, ERA40 datasets and observations recorded at 61 meteorological stations over Vietnam were used to validate the model. The analysis compared seasonal averages o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(9 citation statements)
references
References 25 publications
(26 reference statements)
0
8
0
Order By: Relevance
“…It employs a rotated latitude/longitude horizontal grid with Arakawa B (Arakawa and Lamb, ) staggering and a terrain‐following hybrid‐pressure vertical coordinate described in Simmons and Burridge (). The model horizontal resolution is 25 km with 19 vertical levels (with the lowest level at ∼50 m and the highest at 0.5 hPa), which is the standard model configuration of PRECIS 2.1 as distributed to users (Rao et al ., ; Van Khiem et al ., ; Redmond et al ., ). The Lateral Boundary Conditions (LBC) scheme uses the relaxation method (Davies and Turner, ).…”
Section: Model Description and Tc Identificationmentioning
confidence: 99%
See 2 more Smart Citations
“…It employs a rotated latitude/longitude horizontal grid with Arakawa B (Arakawa and Lamb, ) staggering and a terrain‐following hybrid‐pressure vertical coordinate described in Simmons and Burridge (). The model horizontal resolution is 25 km with 19 vertical levels (with the lowest level at ∼50 m and the highest at 0.5 hPa), which is the standard model configuration of PRECIS 2.1 as distributed to users (Rao et al ., ; Van Khiem et al ., ; Redmond et al ., ). The Lateral Boundary Conditions (LBC) scheme uses the relaxation method (Davies and Turner, ).…”
Section: Model Description and Tc Identificationmentioning
confidence: 99%
“…Previous studies have shown a good ability of RCMs to simulate the regional climate and extreme climate events in Vietnam (Van Khiem et al ., ; Raghavan et al ., ). RCMs have also been used for regional climate projections over Vietnam and found an increase in high‐temperature events and extreme rainfall over most of the country under climate change (Ho et al ., ; Ngo‐Duc et al ., ).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…In [7][8][9][10][11][12][13][14][15][16][17][18][19] [23][24][25]). Projected disappearing climate in the future in Viet Nam is also analyzed in the study.…”
Section: Introductionmentioning
confidence: 99%
“…The RCM system known as 'PRECIS' (Providing Regional Climates to Impact Studies), developed from the Met Office Unified Model (MetUM version 4.7), has been widely used for climate change impact studies in developing countries (Xu et al, 2006;McSweeney et al, 2012;Rao et al, 2014;Van Khiem et al, 2014). A recent study by Redmond et al (2015) used this model, at 25 km resolution, to project the TC activity affecting the SCS and Vietnam under climate change.…”
Section: Introductionmentioning
confidence: 99%